Evaluation Of Character Education Of El-Fash Islamic Elementary School With Cipp Model - Damanik, Sudarman (Dharmas Education Journal (DE_Journal), 2025)
This research aims to determine the evaluation of basic level character education (independent, creative, useful, and honed spiritual aspects) in class III students at El-Fash Islamic Elementary School, South Tangerang City. This research was conducted using a descriptive qualitative approach where questionnaires by parents, documentation and portfolios were used as research instruments. Researchers have the assumption that a value can be called a character that is inherent in students if this value is also applied outside of school so that it becomes a habit. So this assumption will be assessed through a parent questionnaire regarding student habits outside of school. Evaluations produced using the CIPP (Context, Input, Process, Product) method are used to determine whether a program should be replaced, revised or stopped. The use of the CIPP model helps researchers in formulating revisions and matters related to the success or failure of a learning program. The average character score (independent, creative, useful, honed spiritual aspects) based on the vision and mission of El-Fash Islamic Elementary School is 2.0 on a scale of 0-3 (quite effective). Meanwhile, based on the scores from the 2010 Ministry of National Education character aspects, the character education of El-Fash Islamic Elementary School has met all the criteria in question. Therefore, researchers assess that El-Fash Islamic Elementary School has succeeded in carrying out its vision and mission with character and life skills education programs that have been implemented at the elementary level.